Study of Chemical and Mineralogical Composition of Sylvinites of Tubegatan Mine - Xaydarova, Munira D.; Allazov, Rustam Y.; Eshkoraev, Samariddin (International Journal on Orange Technologies, 2024)
The study delves into the chemical and mineralogical composition of sylvinites extracted from the Tubegatan mine. Through x-ray analysis of various components, including sylvinite samples and insoluble residues obtained during experimental melting processes, the research investigates the intricate composition of these materials. By scrutinizing the results of the x-ray analysis, the study unveils crucial insights into the chemical makeup and mineralogical properties of the sylvinites. Furthermore, the research scrutinizes the process of melting different samples of sylvinite to elucidate potential variations in composition and behavior under thermal conditions. This comprehensive analysis provides valuable knowledge essential for understanding the characteristics and properties of sylvinites from the Tubegatan mine, contributing to advancements in the field of mineralogy and facilitating informed decision-making in mining and processing operations.